Blood lipid profile and cardiovascular disease in family history among young people with various health status - M. E. Evsevyeva; E. M. Miridzhanyan; I. V. Babunts; Yu. V. Pervushin (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To study blood lipid profile and cardiovascular disease (CVD) in family history of young people with various health status. Material and methods. The study included 80 people aged 18-29 (mean age 22.3±0.4 years). In all participants, health status screening was performed. According to adaptation potential level, three groups were identified: with good (I), fair (II), and poor (III) adaptation potential. The following parameters of lipidogram were registered: total cholesterol (TCH), high-density lipoprotein cholesterol (HDL-CH), low- and very low-density lipoprotein cholesterol (LDL-CH, VLDL-CH), triglycerides (TG); atherogenicity index (AI) was also calculated. In participants with dyslipoproteinemia (DLP), detailed information on CVD in family history was collected. Results. Adaptation potential was reduced in 56 persons (70%). Abnormal lipidogram (TCH >5.88 mmol/l, LDLCH >3.83 mol/l, and AI >3 U) was observed in 4 participants from Group III (19%), including 3 individuals (14.3%) with TG >1.75 mmol/l (equivalent of Type IIa and III DLP). For all three groups, differences in TCH, LDL-CH, and AI levels were statistically significant. Conclusion. Even in young people, initial symptoms of lipid metabolism abnormality were detected, including hyper- and dyslipidemia. Abnormal lipid metabolism was observed only in young males with poor adaptation potential. Participants with disturbed lipid metabolism had CVD in family history.